Characteristics of the response in patients with major depressive disorder, who have experienced repeated internal displacement, in relation to the change of socio-demographic factors - Chumakova, Ірина (Psychosomatic Medicine and General Practice, 2026)
The goal of this work is to identify the components that contribute to increased psychosocial vulnerability, due to their socio-demographic status acquired by repeated internal displacement, among individuals with major depressive disorder. Between 2024 and 2026, 150 patients suffering with major depressive disorder (MDD) were examined at mental health centers in Luhansk and Rivne; of these, 75 were repeatedly internally displaced (RID) persons, and 75 were patients who had not experienced displacement. Research methods: anamnestic, clinical-psychopathological (using ICD-10 criteria, the M.I.N.I. international neuropsychiatric interview for the assessment of psychotic disorders (Ukrainian version 7.0.2 for DSM-5) and clinical. The study was conducted using semi-structured interviews based on the relevant sections of a patient assessment form that had been developed and tested. These sections covered socio-demographic status (including education, employment, and financial circumstances), family anamnesis, family and social connections’ state. Data obtained was processed using analytical statistical methods, including correlation analysis (t-test, χ²) by “Data analysis” function on Excel. We carried out a comparative analysis of socio-demographic indicators to identify the social, demographic and economic components of psychosocial vulnerability (PV) associated with the social status of patients with MDD who have experienced RID. Among the components of PV related to social status in patients with MDD who have been internally displaced more than once, economic and social predictors of increased PV and, consequently, increased distress have been identified. Thus, a significant and statistically significant reduction was found in the level of satisfaction among RID patients with MDD with their current living and financial conditions and leisure activities at the moment of the examination, compared with the control group (1.47-fold and 1.36-fold, respectively, at p<0.001), which constitutes an additional risk factor for the development of affective disorders, as well as a factor contributing to resistance to antidepressant therapy The results will help us optimize treatment for MDD in people who have been displaced twice, predict treatment’s effectiveness, and identify factors that influence it. Keywords: major depressive disorder, repeated internal displacement, psychosocial vulnerability, distress, resilience, socio-demographic predictors